HPV16 E7‐induced upregulation of KDM2A promotes cervical cancer progression by regulating miR‐132–radixin pathway. Issue 3 (21st August 2018) - Ou, Rongying; Zhu, Linyu; Zhao, Liang; Li, Wenfeng; Tao, Fengxing; Lu, Yiyi; He, Qin; Li, Jianrong; Ren, Yi; Xu, Yunsheng
Abstract : Background: Human papillomavirus (HPV) infection and viral proteins expression cause a number of epigenetic alterations leading to cervical carcinogenesis. The recent discovery of a large amount of histone methylation modifiers reveals important roles of these enzymes in regulating tumor progression. Methods: The changes in expression of 48 histone methylation modifiers were assessed following knockdown of HPV16 E7 in CaSki cells. Lysine‐specific demethylase 2A (KDM2A)‐regulated microRNAs (miRNAs) in cervical cancer pathogenesis were disclosed using quantitative real‐time polymerase chain reaction. The function of KDM2A–miRNAs on cervical cancer was investigated in vitro and in vivo. Results: Upregulation of KDM2A induced by HPV16 E7 promotes cervical cancer cell proliferation and invasion and is correlated with poor prognosis in patients with cervical cancer. KDM2A physically interacts with the promoter of miR‐132 and suppresses its expression by removing the mono or dimethyl group from H3K36 at the miR‐132 locus. Functionally, miR‐132 represses cancer cell proliferation and invasion by inhibiting radixin (RDX). Upregulated KDM2A promotes cervical cancer progression by repressing miR‐132, which results in a derepression of RDX. Therefore, KDM2A functions as a tumor activator in cervical cancer pathogenesis by binding miR‐132 promoter and abrogating its tumor suppressive function. Conclusion: Our results suggest a function for KDM2A in cervical cancer progression and suggest its candidacy as a new prognostic biomarker and target for clinical management of cervical cancer. Abstract : KDM2A–miR‐132–RDX promotes cervical cancer.